PENERAPAN MODEL COOPERATIF LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU DI KELAS IV SDN 105322 DESA MESJID - Laili Fadhillah; Nila Lestari (Jurnal Cakrawala Ilmiah, 2024)
This study aims to apply the Cooperative Learning model to thematic learning on the theme "My Residential Area" and improve the learning outcomes of fourth grade students of SDN 105322 Mesjid Village. Learning improvement activities as many as two cycles on the theme of my residential area through the Cooperative Learning model in fourth grade of SDN 105322 Mesjid Village, Batang Kuis District, semester I of the 2023/2024 academic year were successfully implemented and the results were very satisfying. The improvement in student learning outcomes in participating in learning in each cycle really made researchers and teachers learn a lot. In order to improve learning outcomes, teachers spend a lot of time to be patient in choosing and studying the right model according to the material being taught. The results of this study are that the application of the Cooperative Learning model to the subject of my residential area at SDN 105322 Mesjid Village, Batang Kuis District can foster student learning motivation so that student learning outcomes increase. The learning outcomes in the form of average class scores in the initial conditions in the pre-cycle were only 55%, then increased in Cycle I to 75% and increased again in Cycle II to 95%. The percentage of learning completion in each cycle was very satisfying. The Cooperative Learning learning model can also be applied to other themes